2020
DOI: 10.1159/000510985
|View full text |Cite
|
Sign up to set email alerts
|

Guggulu and Triphala for the Treatment of Hypercholesterolaemia: A Placebo-Controlled, Double-Blind, Randomised Trial

Abstract: <b><i>Background:</i></b> Several herbs are used for lowering high blood cholesterol levels in traditional medicines including Indian Medicine (Ayurveda). We aimed to assess the short-term effects of the combination of Guggulu (<i>Commiphora mukul</i>) and Triphala (<i>Terminalia chebula</i>, <i>Terminalia belerica</i>, and <i>Phyllanthus emblica</i>) on serum cholesterol in healthy subjects with hypercholesterolaemia. <b><i>Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The findings of all these tests were normal. However, Kamali et al (4) observed a substantial reduction in ALT levels in Triphala-treated patients; however, Donato et al (11) found no significant difference in ALT levels between Triphala-treated patients and controls at the end of the study.…”
Section: Secondary Outcomes Only Two Studies (411) Reported the Resul...mentioning
confidence: 88%
See 3 more Smart Citations
“…The findings of all these tests were normal. However, Kamali et al (4) observed a substantial reduction in ALT levels in Triphala-treated patients; however, Donato et al (11) found no significant difference in ALT levels between Triphala-treated patients and controls at the end of the study.…”
Section: Secondary Outcomes Only Two Studies (411) Reported the Resul...mentioning
confidence: 88%
“…The full-text review resulted in the exclusion of two articles: one was a non-RCT, and the other did not assess the outcomes of interest. Therefore, seven English and Thai articles (4,9,11,(21)(22)(23)(24) were considered in our research.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ayurvedic formulations are prepared based on the patient's diet, behavioral changes, patient assessment, detoxification, and rejuvenation condition [16][17][18]. The most widely used herbs to reduce cholesterol are garlic, guggulu, and arjuna [19][20][21]. However, there is no clear evidence for the direct correlation between herbs and hypercholesterolemia [21].…”
Section: Introductionmentioning
confidence: 99%